Programming 32-bit microcontrollers in C exploring the PIC32 - Di Jasio, Lucio (Newnes, 2008)
Embedded control designers have been constantly asking for more performance, more memory and more power to complete ever more advanced applications. Microchip latest and greatest 32-bit architecture, the PIC32, has been designed specifically to fulfill those demands offering an unprecedented level of performance by merging seamlessly the industry acclaimed MIPS 32-bit core with the trusted peripheral and feature set, common to all previous generations of PIC microcontrollers, that has made Microchip a world leader in embedded control. The result is an immediate sensation of familiarity and ease of use for all previous PIC microcontroller users and a refreshing sensation of power and friendliness for all those approaching the 32-bit world for the first time.
Includes bibliographical references and index
Keywords: Microcontrôleurs / Programmation; C (Langage de programmation); COMPUTERS / Programming Languages / C♯; COMPUTERS / Programming Languages / Java; COMPUTERS / Programming Languages / Pascal; C (Computer program language); Microprocessors / Programming; Programmable controllers; C / Programmiersprache; PICmicro; Microprocessors -- Programming; C -- Programmiersprache